The broad landscape of follicular lymphoma: Part I - Fratoni, Stefano; Zanelli, Magda; Zizzo, Maurizio; Sanguedolce, Francesca; Aimola, Valentina; Cerrone, Giulia; Ricci, Linda; Filosa, Alessandra; Martino, Giovanni; Ascani, Stefano (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Follicular lymphoma is a neoplasm derived from follicle center B cells, typically both centrocytes and centroblasts, in variable proportions according to the lymphoma grading. The pattern of growth may be entirely follicular, follicular and diffuse, and rarely completely diffuse. It represents the second most common non-Hodgkin lymphoma, after diffuse large B-cell lymphoma and is the most common low-grade mature B-cell lymphoma in western countries. In the majority of cases, follicular lymphoma is a nodal tumor, occurring in adults and frequently associated with the translocation t(14;18)(q32;q21)/IGH-BCL2. However, in recent years the spectrum of follicular lymphoma has expanded and small subsets of follicular lymphoma, which differ from common follicular lymphoma, have been identified and included in the current 2017 WHO classification. The aim of our review is to describe the broad spectrum of follicular lymphoma, pointing out that the identification of distinct clinicopathological variants of follicular lymphoma is relevant for patient outcomes and choice of treatment.